1997
DOI: 10.1164/ajrccm.156.3.9610013
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Stimulates Sodium Transport and Liquid Clearance in Rat Lung Epithelium

Abstract: Pulmonary edema clearance is driven primarily by active sodium transport out of the alveoli, mediated predominantly by apical sodium channels and the basolateral NA,K-ATPase. We postulated that dopamine, analogous to its effects in other transporting epithelia, could regulate these sodium transport mechanisms and affect lung liquid clearance. We therefore studied the effects of dopamine on sodium transport and liquid clearance in isolated perfused rat lungs. Instillation of dopamine into the airways caused a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 26 publications
9
70
1
Order By: Relevance
“…These findings were associated with increases in Na,K-ATPase function in AT2 cells (5). Similar findings have been reported after treatment of alveolar epithelial cells and lungs with dopamine, dobutamine, and isoproterenol (16)(17)(18). These studies show that increased Na,K-ATPase expression is associated with increased Na,K-ATPase function and lung liquid clearance, suggesting that alveolar Na,K-ATPases play an important role in keeping the alveolus free from edema.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings were associated with increases in Na,K-ATPase function in AT2 cells (5). Similar findings have been reported after treatment of alveolar epithelial cells and lungs with dopamine, dobutamine, and isoproterenol (16)(17)(18). These studies show that increased Na,K-ATPase expression is associated with increased Na,K-ATPase function and lung liquid clearance, suggesting that alveolar Na,K-ATPases play an important role in keeping the alveolus free from edema.…”
Section: Introductionsupporting
confidence: 81%
“…Calculations for isolated-perfused rat model (2,5,(14)(15)(16). Concentration of EBD-albumin was used to estimate airspace volume.…”
Section: Nak-atpase Function In At2 Cells Ouabain-sensitive 86mentioning
confidence: 99%
“…Although only small increases in net ion transport across FDLE monolayers were observed, explants exhibited 50% less expansion over 24 h after DA treatment, suggesting that DAs effects may be of biologic significance. Our data are consistent with previous findings that DA increases fluid clearance in an isolated lung model (11,26), and activates amiloride-sensitive ion transport in alveolar type I cells (27). Our dose-response studies showed small effects of DA at physiologic doses of DA [10 Ϫ8 M to 10 Ϫ7 M (28)], although the effects were not large enough to reach statistical significance.…”
Section: Discussionsupporting
confidence: 92%
“…They secrete many mediators, including dopamine (DA), serotonin, gastrin-releasing peptide (GRP), and somatostatin, (7)(8)(9) which may play a role in the lungs' transition to postnatal life by altering fetal lung epithelial ion and fluid transport. DA concentrations are maximal at birth (10), and it is known to alter alveolar fluid transport by increasing Na ϩ channel and Na ϩ /K ϩ -ATPase activity (10,11). Some studies suggest that serotonin may have a similar role in fluid clearance in the fetal lung (12); however, others suggest that serotonin decreases transepithelial Na ϩ transport (13).…”
mentioning
confidence: 99%
“…Low to moderate doses have dopaminergic effects and have been shown to increase alveolar fluid clearance experimentally (3,4,34). Therefore, the primary analysis of dopamine was done on lungs that had been exposed to low to moderate doses of dopamine.…”
Section: Methodsmentioning
confidence: 99%